Self‐management for non‐cystic fibrosis bronchiectasis - Kelly, Carol (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the efficacy and cost‐effectiveness of self‐management interventions for adults and children with non‐cystic fibrosis bronchiectasis.